15 Bienal de Cuenca bienal del Bioceno : cambiar el verde por azul : 10.12.2021-28.02.2022 - Cazar, Katya (Fundación Municipal Bienal de Cuenca, 2022)
The lines drawn for this 15th edition start from "Bioceno", a concept addressed by Blanca de la Torre for several years, which proposes to move to a new era that places at the center the care of life and the biosphere as a whole. It is an alternative to Antropoceno, a term that overlooks the political, economic and especially colonial implications of the ecological deterioration of the planet and distributes responsibility homogeneously among all anthropos. The subtitle, "Change green to blue" alludes to greenwashing, a corporate strategy that took over the color green, thus changing colors is a symbolic proposal for the construction of a new story. In this Bienal de Cuenca water (blue) has a special role, action in the face of the climate emergency, resistance to extractivist policies, the preservation of biodiversity, the care of the sea, land and air in the face of pollution and the destruction of natural habitats, and a whole socio-environmental narrative much more complex and interconnected than the one that made us believe in green as the color of ecology. The 3 accompanying postcards are of the 3 winning prizes: The People that Is Missing [El pueblo que falta], 2020-2021 / by Cristina Lucas (Spain); Archivo Alexander von Humboldt. Cuenca, 2011-2021 / by Fabiano Kueva (Ecuador); Arpas de agua, 2021 / by Taniana Candiani (México)
Tiraje: 1000 ejemplares
Keywords: Bienal de Cuenca -- 15. -- 2021-2022 -- Cuenca, Ecuador; Geschichte 2006-2021; Klimaänderung; Ökofeminismus; Umweltschutz; Videokunst; Installation -- Kunst; Indigenes Volk; Umweltverschmutzung; Kunst; Ausstellungskatalog -- 10.12.2021-28.02.2022 -- Cuenca, Ecuador; Bildband